Structural, Magnetic, and Optical Properties of Iron-Doped Polyvinyl Alcohol (PVA) Films for Electromagnetic Shielding and Sensor Applications - Amirouche, Bouamer (Journal of Research Updates in Polymer Science, 2025)
Pure PVA and Fe-doped composite films were synthesized using the solution casting method in the present work. Doping with iron (Fe) microparticles at weight percentages of 2% and 6%. The morphological, structural, magnetic, and optical properties of the films were investigated using X-ray diffraction (XRD), vibrating sample magnetometry (VSM), and attenuated total reflection (ATR) spectroscopy. XRD analysis revealed that the crystallite size of the iron microparticles, calculated using the Scherrer equation, was approximately 65.5 nm. Magnetic measurements showed a significant enhancement in saturation magnetization (Ms) from 1.6 x10-2 emu/g (2 wt% Fe) to 8.1x 10-2 emu/g (6 wt% Fe), along with increases in coercivity magnetization. The findings indicate that incorporating iron (Fe) particles into the PVA matrix created a new composite material with typical magnetic behavior. The observations demonstrate the material’s potentiality towards sophisticated functional uses, such as sensors, electromagnetic shielding, and specialized electronic devices.